Review: Formulasi Optimum Sediaan Gel Lidah Buaya (Aloe Vera L.) serta Efektifitasnya Sebagai Obat Luka Pada Hewan Uji - Rahayuni, Ni Putu Dewi; I Wayan Martadi Santika (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Gel preparations are good topical treatments for inflammation. Aloe Vera (Aloe Vera) can be used topically to treat wounds in the form of a gel dosage because it contains mannose-6-phosphate and polysaccharides which function as wound medicine. To obtain the optimum formulation for Aloe Vera gel (Aloe Vera L.) and its effectiveness as a wound medicine in tested animals. Aloe Vera activity as wound healing formulated as a gel preparation for Aloe Vera (Aloe Vera L.) showed that it was able to reduce the size of the burn area on a 5% Na-CMC basis. The Na-CMC based gel formulation had a better speed than the Karbopol-based gel formulation in healing burns.